1990
DOI: 10.1038/ki.1990.8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fish oil on renal growth and function in uninephrectomized rats

Abstract: The basic mechanisms of renal growth remain poorly understood. The work hypertrophy theory holds that after an acute reduction in renal mass, the growth of the kidney occurs as a consequence of increased renal function. Pharmacological inhibition of renal prostaglandin synthesis impairs the acute adaptive increases in both renal function and mass following partial nephrectomy. The present study examines the effects of four weeks of dietary fish oil on renal growth, function and arachidonic acid metabolites in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Likewise, increased renal lipid synthesis in the absence of hyperlipidaemia resulted in renal disease 6, thus pointing to the importance of cellular lipid metabolism 7. In addition, lipid abnormalities occurring in several animal models of kidney disease were shown to contribute significantly to renal injury 8–13. In humans, evidence is still sparse.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, increased renal lipid synthesis in the absence of hyperlipidaemia resulted in renal disease 6, thus pointing to the importance of cellular lipid metabolism 7. In addition, lipid abnormalities occurring in several animal models of kidney disease were shown to contribute significantly to renal injury 8–13. In humans, evidence is still sparse.…”
Section: Introductionmentioning
confidence: 99%
“…It remains unclear whether this adaptive response is dependent on established hypertrophy or hormonal-humoral mediators. A recent ani mal study showed that augmentation of the compensatory increases in renal function observed with fish oil feeding was not associated with any additional renal hypertrophy [6]. Thus, hyperfunctioning after unilateral nephrectomy seems to be independent of renal growth.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the pronounced glomerular sclerosis and reduced renal plasma flows indicate renal microvascular damage, the increased relative kidney weights in the fish oil group after 32 weeks without concomitant glomerular hypertrophy point to an increased interstitial cell proliferation and/or increased matrix synthesis, although the latter have not been directly assessed in this study. Another explanation for the increased kidney weight could be a direct effect of the altered PG metabolism on kidney growth, as proposed by Logan et al [20].…”
Section: Effects Of Fish Oil In the Milanmentioning
confidence: 98%
“…Also an induction of extra-or intrarenal growth factors is possible which could account for an increased kidney weight and accelerated renal fibroblast proliferation. The results of Logan et al [20] show that, already after 4 weeks of fish oil diet, in healthy Sprague-Dawley rats the clearance in relation to the kidney weight was reduced, and the increased kidney weight, therefore, could not be explained by the work hypertrophy concept [21]. Moreover, fish oil has been shown to possess immunomodulating properties, and on the one hand the inhibition of proinflammatory cytokine and leukotriene [22] as well as superoxide production [see ref .…”
mentioning
confidence: 99%
See 1 more Smart Citation